2006
DOI: 10.1143/jjap.45.5836
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Piezoelectric Energy Harvesting Using Cymbal Transducers

Abstract: This study reports the experimental and analytical results on a piezoelectric cymbal with 29 mm diameter and 1 mm thickness operating under force of 70 N in the frequency range of 10–200 Hz. It was found that the generated power increases with the frequency and around 100 mW can be harvested at frequency of 200 Hz across a 200 kΩ resistor. Power generation from the cymbal transducer was modeled by using the theory developed for the Belleville spring. The calculated results were found to be in good agreement wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(47 citation statements)
references
References 1 publication
0
45
0
2
Order By: Relevance
“…More recently, energy harvester designs and models of the Cymbal transducers have also been introduced. Studies have shown their feasibility for energy harvesting because of their high reliability and small deviation in long term usage [11,[26][27][28]. In this article we present a Cymbal type energy harvester component aimed for mounting in a shoe insole.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, energy harvester designs and models of the Cymbal transducers have also been introduced. Studies have shown their feasibility for energy harvesting because of their high reliability and small deviation in long term usage [11,[26][27][28]. In this article we present a Cymbal type energy harvester component aimed for mounting in a shoe insole.…”
Section: Introductionmentioning
confidence: 99%
“…The recent progress in power harvesting from mechanical vibration to power generation was performed at Pennsylvania State University. [8][9][10] These studies were made on a cymbal transducer having a ceramic dise with a diameter of 29 mm and 1 mm thickness. A power of 39 mW can be transferred across the low impedance load under a dynamic force of 7.8 N at 100 Hz.…”
mentioning
confidence: 99%
“…Prior studies on the cymbal transducer have mostly utilized finite element simulation and experimental methods (Fernandez et al 1998;Kim et al 2004;Kim, Priya, and Uchino 2006;Luo et al 2007;Sun et al 2005;Zhao, Yu, and Ling 2010) to predict the behavior of cymbal shape. However, a simplified analytical model is lacking that can be used on a regular basis for the design and performance optimization.…”
Section: Modelingmentioning
confidence: 99%
“…However, for d 31 mode transducers, mechanical amplifiers can be used to manipulate the input forces, as exemplified in the cymbal transducer. Instead of using the cymbal shape to increase displacements as an actuator (Fernandez et al 1998;Sun et al 2005), it can be used to increase the force on the piezoelectric materials as an energy harvester (Kim et al 2004;Kim, Priya, and Uchino 2006;Zhao, Yu, and Ling 2010). It has been shown that rather than using a circular cymbal, a rectangular cymbal could be used to take better advantage of the crystal orientation in the piezoelectric material (Luo et al 2007).…”
Section: Introductionmentioning
confidence: 99%